Left-right symmetry breaking: learning from the chicken - Pieper, Tobias Karl; Tsikolia, Nikoloz (Frontiers in Cell and Developmental Biology, 2025)
Morphological left-right asymmetry of visceral organs in most cases reveals a typical arrangement. This implies directed symmetry breaking which is suggested to be based on the existence of structural chirality. At early developmental stages many vertebrate model organisms display so-called leftward flow of extracellular fluid which is based on the unidirectional rotation of chiral cilia. Cytoskeletal chirality has been shown to contribute to the left-right asymmetry of invertebrates including Caenorhabditis elegans and Drosophila melanogaster. The mechanisms of left-right symmetry breaking in vertebrates without ciliary flow remain mysterious. Here, we present our perspective on left-right patterning and symmetry breaking in the chick within a broader context.